Solo travel: extraordinary experiences and personal transformation - Sanchez de Rojas, Isadora Matsuda (2020)
The purpose of this research is to analyze the transformative and enduring effects of extraordinary experiences. For this, the extraordinary experience of solo travel was explored, defined in this work as traveling alone for a period of time (although the meaning of the experience is more relevant to the study than the duration of the trip). The intention of the study was to understand how extraordinary experiences can transform the individual. For this, sixteen in-depth interviews were conducted with people who had significant experiences while traveling alone. The interviewees described their motivations, the most remarkable experiences, feelings, reflections, meanings and the results of solo travel. The results showed that being alone contributed to states of self-reflection and immersion during the experience, leading to skill and knowledge acquirement, reflection on pre-established values and behaviors, playing with possible selves and the development of new goals and models of life. This study collaborates with the literature by theorizing the transformative effects of extraordinary experience as a rite of passage, since solo travelers go through the phase of separation - where they disengage from their ordinary lives; transformation - experiences lived during solo travel that had a transforming role in individuals; and incorporation - to the new personality, values, beliefs, social roles and status.